Synthesis and Dipolymer Structure of Salen-type N2O2 Ligand 2,2'-[(Pentane-1,5-diyldioxy-bis)-bis-(nitrilomethylidyne)]dinaphthalene - Zhao, Li; Zhang, Yu-Jie; Zhang, Shou-Ting; Guo, Hong-Xia; Cheng, Qian (Asian Journal of Chemistry, 2013)
The compound, 2,2'-[(pentane-1,5-diyldioxy-bis)-bis-(nitrilomethylidyne)]dinaphthalene has been synthesized by 1,5-bis-(aminooxy)pentane and 2-naphthaldehyde in ethanol solution and characterized structurally by X-ray crystallography. The molecule of the title compound, C27H26N2O2, assumes a dipolymer structure through a weak C-H···C hydrogen-bonding interactions. And the single crystal structure of the compound revealed all-conformation of the (-CH=N-O-(CH2)5-O-N=CH-) linkage, which resulted in the structure with two nitrilomethylidyne units apart from each other. The compound is sufficiently stable to resist scrambling of the C=N bonds. This may be ascribed to lower reactivity of the C=N-O bonds toward nucleophiles.